Bortezomib, thalidomide, and dexamethasone versus thalidomide and dexamethasone for response rates in multiple myeloma patients: a retrospective study - Juan M. Cano-Calderón; Juan F. Zazueta-Pozos; Adán G. Gallardo-Rodríguez; Carlos Martínez-Murillo; Irma Olarte-Carrillo; Adolfo Martínez-Tovar; Christian O. Ramos-Peñafiel (Revista Médica del Hospital General de México)
Introduction: The most current treatment of multiple myeloma is based on a combination of drugs, including immunomodulators and proteasome inhibitors. The bortezomib, thalidomide, and dexamethasone (VTD) and thalidomide and dexamethasone (TD) regimens are commonly used as a first-line treatment due to limited resources. Objective: To compare the proportion of favorable responses, survival, and time to the next treatment between two different treatment approaches. Materials and methods: Retrospective study based on medical records of patients with multiple myeloma, eligible for stem cell transplantation, who received, first-line, the VTD or TD combination. Results: A total of 83 patients were analyzed. The average age was 57 years. The most common type of MM was immunoglobulin G kappa (79.5%), and 51.8% had an International Staging System score of 3. At diagnosis, 28.9% had renal failure, and 42.2% had albumin levels < 3 g/dL. 37.3% were treated with the TD regimen, whereas 62.7% received the VTD regimen. It was considered that 53% had a favorable response. However, patients treated with ETV showed a higher proportion of responses (54.8% vs. 39.3%, p = 0.011). Regarding survival, no differences were identified between the two treatments (Log Rank 0.076) or between the times until the next treatment (Log Rank 0.288). Conclusion: The VTD scheme was superior to the TD scheme, presenting response ratios similar to other series worldwide. This makes it a viable option for patients with limited financial resources.